(untitled) (PUBMET, 2025)
As shown by the Open Access (OA) Diamond Journals study, which considers OA journals to be journals that are “free for the reader and for the author”, the landscape of academic publishing turns out to be much more diverse and rich than indicated by Research Assessment (RA) quantitative methods, such as the Impact Factor (IF). Indeed, RA policies relying mostly on the IF favour wellestablished journals supported by big publishers, and corresponding to a specific profile: Western, English-speaking, and primarily STEM focused journals. The Diamond OA model, on the other hand, represents a community-driven and scholar-led publishing model that is equitable and diverse (e.g. in terms of languages, and countries represented), capable of transforming the global publishing ecosystem towards a more equitable, diverse and scholar-owned future. In this sense, supporting and increasing Diamond OA journals’ quality and visibility means transforming not only the perception of the academic landscape but also the way RA policies are defined.